Construction and Writing Flaws of the Multiple-Choice Questions in the Published Test Banks of Obstetrics and Gynecology: Adoption, Caution, or Mitigation? - Balaha, Magdy H.; El-Ibiary, Mona T.; El-Dorf, Ayman A.; El-Shewaikh, Shereef L.; Balaha, Hossam M. (Avicenna Journal of Medicine, 2022)
Background The item-writing flaws (IWFs) in multiple-choice questions (MCQs) can affect test validity. The purpose of this study was to explore the IWFs in the published resources, estimate their frequency and pattern, rank, and compare the current study resources, and propose a possible impact for teachers and test writers.Methods This cross-sectional study was conducted from September 2017 to December 2020. MCQs from the published MCQ books in Obstetrics and Gynecology was the target resources. They were stratified into four clusters (study-book related, review books, self-assessment books, and online-shared test banks). The sample size was estimated and 2,300 out of 11,195 eligible MCQs were randomly selected. The MCQs (items) were judged on a 20-element compiled checklist that is organized under three sections as follows: (1) structural flaws (seven elements), (2) test-wiseness flaws (five elements), and (3) irrelevant difficulty flaws (eight elements). Rating was done dichotomously, 0 = violating and 1 = not violating. Item flaws were recorded and analyzed using the Excel spreadsheets and IBM SPSS.Results Twenty three percent of the items (n = 537) were free from any violations, whereas 30% (n = 690) contained one violation, and 47% (n = 1073) contained more than one violation. The most commonly reported IWFs were “Options are Not in Order (61%).” The best questions with the least flaws (75th percentiles) were obtained from the self-assessment books followed by study-related MCQ books. The average scores of good-quality items in the cluster of self-assessment books were significantly higher than other book clusters.Conclusion There were variable presentations and percentages of item violations. Lower quality questions were observed in review-related MCQ books and the online-shared test banks. Using questions from these resources needs a caution or avoidance strategy. Relative higher quality questions were reported for the self-assessment followed by the study-related MCQ books. An adoption strategy may be applied with mitigation if needed.
Keywords: multiple-choice questions writing flaws; multiple-choice questions violations; test bank quality